Transforming state responses to feminicide : women's movements, law and criminal justice institutions in Brazil - Macaulay, Fiona, 1962- (Perspectives on crime, law and justice in the Global South, 2021)
State responses to feminicide in Latin America, characterised in many cases by indifference and incompetence, have caused global concern. This book provides a new and refreshingly positive story from the region by tracing the transformation of state responses to feminicide in Brazil. It is the first single country study to examine in detail how strategic action by the women's movement has resulted in significant improvements in the investigation, prosecution and prevention of domestic violence and feminicide. Fiona Macaulay showcases the main contributory factors to the development of criminal justice best- practices around feminicide. She demonstrates the combined impact of regional efforts, local women's movement mobilisation, changes in the law and its application, and the action of policy entrepreneurs within the criminal justice institutions. Drawing on her knowledge of pioneering coalitions of interest involving feminist academics, NGOs, local campaigners, bureaucrats, politicians, police and prosecutors, the author unveils how these actors were able to identify, create and use institutional spaces to ensure long- lasting positive change. This book is a must- read for activists and researchers interested in practical strategies for improving criminal justice responses to gender- based violence, gender- aware police reform, comparative and feminist criminology, and the social and institutional dynamics of violence in Latin America.